Synthesis of Silver Nanoparticles from Cucumis melo L. and Assessment of Its Antimicrobial Properties - Haryani, Yuli; Nabella, Iswatun; Yuharmen, Yuharmen; Kartika, Ganis F. (Pharmacology and Clinical Pharmacy Research, 2018)
Over the past decade, the use of biological agents such as plants, cyanobacteria, bacteria, and fungi for synthesis of metal nanoparticles has been developed. The aim of this study was to investigate antibacterial activity of Cucumis melo L. peel extract and its nanoparticles formulation against Eschericia coli. The nanoparticles were made using silver nitrate with the ratio between C. melo L. extract and silver nitrate aqueous solution (1 mM) were 1:10 and 1:15. The formation of silver nanoparticles was observed after microwaved for 30, 60, 90, 120, 150, and 180 seconds by visible spectrophotometry analysis. Phytochemical screening revealed the presence of flavonoid and terpenoid within the extract. However, the characteristic of surface plasmon resonance band, which occurs in the range of 410-500 nm were not found in the nanoparticle extract, even though the reaction time was extended to 330s. Antibacterial activity against E. coli of the extract and its nanoparticle formulations was determined using Resazurin microtiter assay and compared to Amoxsan® as positive control. The highest E. coli inhibition was exhibited by the nanoparticles (79.8739±0.3859), followed by the extract (65.2821±0.9949). The nanoparticles and the extract have potent antibacterial activity compared to positive control (84.5519 ± 0.2544). In conclusion, the antibacterial activity of the C. melo L. silver nanoparticles formulation was better than its extract.Keywords: Cucumis melo, silver nanoparticles, UV-Vis spectra